Cause-Related Marketing and Purchase Intention : A Study on Indian Millennials - Bakshi, Megha; Verma, Rajesh (Prabandhan: Indian Journal of Management, 2023)
Purpose: This research initiative aimed to delve into three crucial areas of investigation. First, it sought to analyze how cause-related marketing (CrM) influenced the purchase intentions of Indian millennials. Secondly, it strove to assess the nuanced role of the warm-glow phenomenon as a mediating factor concerning purchase intentions associated with CrM activities. Lastly, it aimed to comprehensively analyze how gender disparities moderated the impact of warm glow (WG) on the intricate interplay between CrM efforts and purchasing tendencies among the Indian consumer demographic. Design/Methodology/Approach: Convenience sampling was employed to gather digital data through various online platforms, including social media. The final dataset, which included responses from millennials from Punjab, was carefully collected. SPSS 25 and Smart PLS 4.0 were used to validate the influence of CrM on purchase intentions and determine the complex role played by warm-glow dynamics. The potential gender disparities were thoroughly scrutinized using the measurement invariance in composite models and multi-group analysis techniques. Findings: The study’s outcomes revealed a compelling narrative: CrM significantly influenced individuals’ purchase intentions. An in-depth investigation of the mediation research revealed that the WG mechanism functioned as an extensive mediator, closely connecting PI propensities and CrM efforts. The relationships between these dimensions revealed a clear gender impact. Research Limitations/Implications: Businesses could effectively use different societal issues to align with product sales, which was a significant indication of the importance of CrM and the WG it produced in molding buy intentions. Addressing societal concerns, including customers in furthering Sustainable Development Goals (SDGs), and producing profits were the three results of this interdependent relationship. Practical Implications: It was suggested that CrM effectively provided customers with avenues and incentives to attain the value-based benefits they sought, whether directly tied to their primary purchase intent or as additional outcomes. Our study has its limitations and presents possibilities for future researchers to explore. Investigating whether this innovative business strategy has the potential to address environmental challenges and achieve SDGs could be a focus of future research. Originality/Value: This study presents data from an emerging economy and developed a model to examine millennials’ perceptions of CrM-linked purchase intentions as well as the dynamic interaction of WG, gender, CrM, and purchase intentions. This study departed from earlier research on CrM.